Hand Gesture Recognition - Aashima Gupta,; Krishna Balaji,; Preeti Kalra, (International Journal of Scientific Research in Science and Technology, 2024)
One technology that has grown significantly in recent years and garnered a lot of attention is gesture recognition. Recognizing human movements is the primary goal of gesture recognition technology. An overview of gesture recognition, its various applications, how the system operates, applications, the suggested idea, the hardware and software tools needed to implement it, the idea's benefits and drawbacks, and the gesture recognition system's future potential are all covered in this paper.
Keywords: Hand Gesture Recognition; Python, Opencv; Mediapipe; Pyautogui; Screen Brightness Control